The Breaking Down Political Corruption: The Urgency of Progressive Law Enforcement - Abdul Wahid (Rechtsidee, 2021)
Political corruption is one of the legal phenomena in the form of corruption carried out by involving political actors or power actors. Political corruption is a phenomenon that occurs in almost all parts of the world and is a global problem. This study aims to explore the value and substance of progressive law as a solution in dealing with political corruption in Indonesia. This research is a normative legal research. This research specifically prioritizes socio-legal aspects, namely non-legal aspects that can enlighten and clarify the description of problems in political corruption. The legal materials used are primary legal materials which include: the Corruption Law, the Amendment to the Corruption Crime Act, and the UNCAC ratification law. Secondary legal materials include the results of studies and research on political corruption in Indonesia, and non-legal materials include various non-legal studies and analyzes related to political corruption that support this research. The approach used is a statutory approach as well as a conceptual approach. The results of the study confirm that the urgency of progressive law in breaking down political corruption needs to be carried out because the orientation of progressive law does not only focus on rules, but also emphasizes behavioral aspects. The orientation and formulation of progressive law in breaking down political corruption is to emphasize the behavioral dimension in the form of leadership and professionalism in terms of substance, structure, and legal culture.